Perceived emotional competence and competition appraisals as predictors of stress-recovery balance in sports - Niemi, Janna-Carla (2021)
Athletes’ emotional responses play an important role in sport performance. An athlete’s ability to identify, understand, and regulate their feeling states, called emotional competence, can have an influence on their performance related experiences. The way in which athlete appraises a competition situation and their options to deal with the task demands also determines their experiences in that situation. The purpose of this thesis was to examine the relationship among perceived emotional competence, stress-recovery balance, and competition appraisals. Two hundred and two athletes (141 males, 62 females, Mage = 20.92, SD = 6.24) took part in this study. They filled out a multi-scale questionnaire assessing the study variables. Positive correlations were found among emotional competence, challenge appraisal, and recovery (general and specific), and negative correlations were found between threat appraisal and stress (general and specific). A multiple regression analysis was conducted to examine the relationship among perceived emotional competence, competition appraisals, and stress-recovery balance. Results indicated that all three variables were correlated and that perceived emotional competence and competition appraisals were significant predictors of athletes’ stress-recovery balance. In the present study 25 % of variance in stress and 28% of variance in recovery was predicted by perceived emotional competence and competition appraisals. The study results were in line with previous research and provided important information in understanding the relationship among athletes’ stress-recovery balance, perceived emotional competence, and athletes’ competition appraisals. These study results bring to light the importance of appraising situations as challenge for athletes’ recovery and the importance of developing athletes’ emotional competence skill to help them in handling stress and recovering from it. Additionally, practical implications, study limitations, and future research directions have been discussed.